1996
DOI: 10.1190/1.1443957
|View full text |Cite
|
Sign up to set email alerts
|

A special circumstance of airborne induced‐polarization measurements

Abstract: Airborne induced‐polarization (IP) measurements can be obtained with standard time‐domain airborne electromagnetic (EM) equipment, but only in the limited circumstances when the ground is sufficiently resistive that the normal EM response is small and when the polarizability of the ground is sufficiently large that the IP response can dominate the EM response. Further, the dispersion in conductivity must be within the bandwidth of the EM system. One example of what is hypothesized to be IP effects are the nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 9 publications
1
31
0
1
Order By: Relevance
“…Efetua medições no domínio do tempo -ATDEM (Palacky & West, 1991;Smith & Klein, 1996). Sua vantagem sobre um sistema que trabalha no domínio da freqüênciaé que ele emite sinal num espectro de freqüências contínuo.…”
Section: Dados Aeroeletromagnéticosunclassified
“…Efetua medições no domínio do tempo -ATDEM (Palacky & West, 1991;Smith & Klein, 1996). Sua vantagem sobre um sistema que trabalha no domínio da freqüênciaé que ele emite sinal num espectro de freqüências contínuo.…”
Section: Dados Aeroeletromagnéticosunclassified
“…The possibility of extracting chargeability information from transient EM data has, thanks to its potentially significant impact to mineral exploration, kept its appeal over time (Flis et al, 1989, El-Kaliouby et al, 1997, with a late shift in interest from ground to airborne data (Smith andKlein, 1996, Kratzer andMacnae, 2012). The common understanding is that, in favourable conditions, it might be possible to recover some IP parameters, mainly the chargeability m, from airborne TEM data.…”
Section: Introductionmentioning
confidence: 99%
“…While early papers speculated that particular conductivity distributions or magnetic effects could cause this effect, Weidelt (1982) showed that for a coincident loop system with a step-off primary field, the measured secondary field must be of a single sign over non-polarizable ground regardless of the subsurface distribution of conductivity. This property can also be extended to centre loop systems, including many airborne systems (Smith & Klein, 1996). Negative transients are commonly observed in airborne TEM systems, such as Fugro's AeroTEM system or Geotech's VTEM system.…”
Section: Introductionmentioning
confidence: 99%